Deontology for teachers. (Journal of Parents and Teachers, 2014)
Education is an ethical phenomenon, in which values must prevail. Schools are, therefore, communities and places of learning in which human development is promoted. However, and because of the ethical crisis experienced by our world today, the school is forgetting this facet. Therefore, the article explains the deontology of teachers and offers a decalogue of the good educator.
Keywords: Education; ethics; values; crisis of values; deontology; decalogue.